Efeito do tratamento com laser de baixa potência e ultrassom na cicatrização de feridas em ratos com e sem diabetes - Fantinati, Marcelo Silva (2015)
Injuries from third degree burns in individuals with diabetes mellitus are considered complex wounds, difficult natural repair and take a long time for the total tissue reestablishment. To minimize the time and improve the biological effects in the healing process, this study aimed to evaluate the effects of laser low power and low-intensity ultrasound in healing wounds by third-degree burns in rats with and without diabetes. This study was approved by CEUA-PRPPG-UFG and used 150 adult female rats. These rats were divided into four groups of 25 animals each: control group not diabetic; group treated with laser non-diabetic ; group treated with ultrasound non-diabetic , diabetic control group; diabetic group treated with laser and diabetic group treated with ultrasound. All animals received an occlusive dressing on all experimental days. The therapy was with laser GaAlAs diode-650 nm-12 mW, creep 3 J/cm2 until day 7 and 6 J/cm2 for the following day, on alternate days it was the ultrasound therapy with 3 MHz pulse emission frequency of 100 Hz modulated to 20% at a dose of 0.5 W/cm2 for three minutes. The treatments with diabetes were experimentally induced with intraperitoneal estrepzotocina (40 mg/Kg). The wounds were assessed at 3, 7, 14, 21 and 30 days after the burn from scalding and sacrificed for the morphometric, macroscopic and microscopic analysis. The contraction of the wound and the amount of collagen was significantly increased in all experimental days the groups treated with either laser ultrasound as compared to control animals, with or without diabetes, and the microscope, it can be seen that angiogenesis and fibroblasts were significantly higher in the proliferative phase of the laser-treated group compared with the control animals with diabetes, mononuclear cell infiltration and, angiogenesis and fibroblasts were higher in groups treated with ultrasound as compared with the controls or the animals without diabetes. It follows that the US has greater efficacy in inflammatory and proliferative phase when compared to the LBP but in wound remodeling phase, LBP best modulates the inflammatory process and hence an efficient healing.